Dihydroartemisinin loaded layered double hydroxide nanocomposites for tumor specific photothermal–chemodynamic therapy. Issue 48 (18th November 2020) - Lu, Jingsong; Guo, Zhenhu; Che, Shenglei; Gao, Fei; Gu, Zi; Xu, Jianzhong; Chi, Yongjie; Xu, Wanling; Zhang, Junxin; Takuya, Nonaka; Yu, Jing; Zhao, Lingyun
Abstract : With the inspiration to develop new cancer nanotherapeutics by repurposing old drugs, in the current study, we proposed dihydroartemisinin loaded layered double hydroxide with peroxide self-supplying property for enhanced photothermal–chemodynamic therapy. Abstract : With the inspiration to develop new cancer nanotherapeutics by repurposing old drugs, in the current study, a novel two dimensional nanomedicine namely Mn doped, dihydroartemisinin (DHA) loaded layered double hydroxide (MnMgFe-LDH/DHA) with peroxide self-supplying properties for enhanced photothermal–chemodynamic therapy was proposed. Such nanostructures could be synthesized by a simple coprecipitation method, and the as-prepared MnMgFe-LDH/DHA exhibits excellent photothermal properties with a photothermal conversion efficiency up to 10.7%. Besides, the in situ reaction between the released DHA and Fe 2+ /Mn 2+ produced by the degradation of LDH can lead to a burst of intracellular reactive oxygen species (ROS) by Fenton-like reactions. Furthermore, the in vivo experiments demonstrate that MnMgFe-LDH/DHA exhibits a remarkable chemodynamic/photothermal therapy (CDT/PTT) synergistic effect on tumor treatment with negligible damage to normal tissues. Finally, this research provides a smart strategy to construct a DHA repurposing nanomedicine for tumor specific treatment.